(3GdETGQGJ Edi eG hbY aj GdefgGL ef GdCSeGA hGdCeGcf hGddZGJs - (3YeQ Hf Ydj Hf CMeO GdCfUGQj GdTGaYj, SQGL GdOjf, CHh MaU GHf GdfMhj, GdeYQha HGHf Gdedbf, J (B804 (3g` s ((3GdeOQSI GdXGgQjI s)
(3ChdgG (B:s
(3hHYO acJGH GdefgGL ddYdGeI eMi GdOjf GdfhhihbO JjSQ di Ydjg YOI eDdaGJ s
(3BNQgG (B:s
(3hGdeQGO Hbhdge eHbGJ MLGL Gdjef Hdede Gi eHbGJ Cgd JgGeI dCf dGf Cgd Gdjef ejbGJge bQf s
(3GNJUQ ajg cJGHg fgGjI GdeMJGL hbSeg Edi KdGKI GbSGe JJHChd dZGJg GdYQHjI hGdeYQHI hGdCdaGX GdehdOI hGdebUhQ hGdeeOhO hGdeLehY hGdeaQOs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs